Asymmetric Effects of Oil Price, Exchange Rate and Money Volume on Stock Returns of Tehran Stock Exchange - Masoumeh Shirinpour; Gholamali Haji; Ahmad Sarlak; Hamidreza Alipour (Environmental Energy and Economic Research)
The main purpose of the present study is to investigate and analysis the impact of oil price fluctuations and exchange rates as well as monetary policies on the performance of the Tehran stock exchange. To this end, monthly information on the variables of oil price, exchange rate, liquidity and stock returns in the Tehran Stock Exchange in the period of April 2008 to March 2020 were collected. The results of the research model estimate using the nonlinear Markov switching approach indicated that the exchange rate in both regimes has a positive and significant effect on market stock returns. Oil price fluctuations in the first regime have a negative and significant effect, and in the second regime, it has a positive and significant effect on market stock returns. Finally, the share of monetary instruments as an indicator of monetary policy in changes in stock returns was estimated to be less than 10%.